2014
DOI: 10.1002/aic.14656
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on liquid flow characteristics in microtubes

Abstract: in Wiley Online Library (wileyonlinelibrary.com)The fundamental understanding and prediction of liquid flow characteristics in microscale are important to control the performance of microfluidic devices. However, fundamental questions about liquid flow characteristics in microscale have not been settled yet and systematical investigation is needed. A systematical investigation on liquid flow characteristics through microtubes with diameters varying from 44.5-1011 lm and relative roughness in the range 0.02-4.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 90 publications
(312 reference statements)
0
5
0
Order By: Relevance
“…The discrepancies in the curves for G values from 300 to 800 kg/m 2 s, corresponding to Reynolds numbers ranging from 100 to 300 (i.e., laminar flow), may be due to an early transition behavior between laminar and turbulent flows for 200 < G < 700 kg/m 2 s, as described by [28][29][30]. Cheng et al [31] reported similar results from other works and related them to the smaller dimensions of the microchannels.…”
Section: Resultsmentioning
confidence: 57%
“…The discrepancies in the curves for G values from 300 to 800 kg/m 2 s, corresponding to Reynolds numbers ranging from 100 to 300 (i.e., laminar flow), may be due to an early transition behavior between laminar and turbulent flows for 200 < G < 700 kg/m 2 s, as described by [28][29][30]. Cheng et al [31] reported similar results from other works and related them to the smaller dimensions of the microchannels.…”
Section: Resultsmentioning
confidence: 57%
“…In contrast, mixed reports can be found when looking at flow in microtubes with i.d. smaller than 50 µm where, for instance, Chen et al [11] confirm the applicability of the HagenPoiseuille theory to analyze the flow of deionized water in a poly-ether-ether-ketone tube with an i.d. of 44.5 µm, whereas Zhigang et al [12] report the opposite behavior for the flow of distilled water in a quartz glass microtube with an i.d.…”
Section: Introductionmentioning
confidence: 78%
“…[1][2][3][4] Microfluidic devices, as understood herein, refer to fluidic devices over a scale ranging from microns to a few millimeters, or more specifically in the range of about 10 microns to about 2 millimeters. 5 Some key microfluidic devices that have been used in large-scale production include the Corning Advanced-Flow Reactor (solketal tertbutyl ether, 12 kg/h), 6 Forschungszentrum Karlsruhe (FZK) reactor (polymer intermediate, 30 tons/week), 7 …”
Section: Introductionmentioning
confidence: 99%
“…1−4 Microfluidic devices, as understood herein, refer to fluidic devices over a scale ranging from microns to a few millimeters, or more specifically in the range of about 10 μm to about 2 mm. 5 Some key microfluidic devices that have been used in large-scale production include the Corning Advanced-Flow reactor (AFR) (solketal tert-butyl ether, 12 kg/h), 6 the Forschungszentrum Karlsruhe (FZK) reactor (polymer intermediate, 30 tons/week), 7 Alfa Laval Plate Reactor or Open Plate Reactor (sodium sulfate, ∼5 kg/h), 8 the IMM cylindrical falling film microreactor (nitroglycerine, 15 kg/h), 9 and Ehrfeld BTS MIPROWA systems (10−10000 L/h). 10 The aforementioned reactor systems are characterized by various channel geometries, diverse mixing and heat exchange designs, and thus distinctive scale-up strategies.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation